Penerapan Sistem Informasi Akuntansi Berbasis Android SIAPIK Pada Toko Kardi - Devi Giman; Ayu Rakhma Wuryandini; Sahmin Noholo (Economics and Digital Business Review, 2024)
This study aims to determine 1) Forms of accounting information systems in Kardi Stores, 2) Application of accounting information system based on android SI APIK at Kardi Store, and 3) Comparison of the old system and the new system at Toko Kardi. The data analysis used in this research is a descriptive qualitative approach. By using primary data sources and secondary data sources. The data collection method in this study was carried out by means of observation, interviews, and documentation. The results showed that: (1) Accounting records or accounting practices at Toko Kardi are not system-based or still in the use of simple and undetailed records, so that the profit or turnover obtained at the store cannot be accurately ascertained, it can only be estimated more or less. (2) The application of the SI APIK android-based accounting application can help Toko Kardi in processing transactions automatically into financial information in the form of accurate financial reports according to SAK EMKM. (3) The manual system is considered less effective because not all transactions can be recorded directly, there is potential for fraud, security and data inaccuracies. In the new system, information can be more easily accessed and understood because the output of financial reports is already available. Then there is a database within the program where all monetary transaction records can be stored safely for future reference. Users from the micro, small and medium enterprise sector can easily access historical records from any location at any time